Efficacy of flexible ureteroscopy and laser lithotripsy for lower pole renal calculi. (November 2014) - Sahai, A; Khan, F; Anjum, F; Dickinson, IK; Marsh, H; Sriprasad, S
Objective: Our aim was to determine whether flexible ureterorenoscopy and laser lithotripsy is efficacious and safe in treating lower pole renal calculi. Materials and methods: Patient, procedure and stone data of patients who underwent flexible ureterorenoscopy and laser lithotripsy at our referral centre were collected prospectively between November 2005 and November 2011 and entered into a designated database. In all, 242 procedures were performed in 198 patients. Results: The mean age was 51.2 years. The mean calculi size was 10.51 mm (range 4–27 mm). Thirty seven patients had more than one stone in the lower pole. An access sheath was used in 19 patients (9.6%), 171 (86.4%) had a ureteric stent inserted after the procedure, and 165 patients had a single procedure. Re-operation rate was 16.7%. Stone-free rates after one procedure were 89%, 80% and 41%, respectively, for calculi measuring 4–10 mm ( n =107), 11–20 mm ( n =76) and > 20 mm ( n =15). The overall stone-free rate was 83%, 91% and 95% after one, two and three procedures, respectively. Conclusion: Flexible ureterorenoscopy and laser lithotripsy is a safe and effective minimally invasive treatment option for patients with 4–20 mm lower pole calculi. Staged procedures, however, become necessary as the size of the stone increases greater than 20 mm, and this should be mentioned when counselling patients for their primary procedure.